GOVERNMENT MARKETING (Gov-Mark 9Ps): Adaptation of Public Sector Marketing Model to City Appearance Branding Policy - Wihana, Dadang; Ilham, Muh; Nurdin, Ismail; Sartika, Ika (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
This research focuses on the application of public sector marketing in the smart branding policy in Depok City, West Java Province. The main objective of this research is to analyze public sector marketing on smart branding policies with a focus on city appearance branding. This research is based on public sector marketing theory, specifically the 7Ps marketing mix (Product, Price, Place, Promotion, People, Physical Evidence, Process) from Kotler and Lee, Booms and Bitner, as well as city appearance branding theory from Ahmadjayadi and Kavaratzis. The method used is descriptive qualitative with data collection through in-depth interviews, observation, Focus Group Discussion (FGD), and documentation. Data analysis was conducted using NVivo 14 software to identify patterns and themes. The results showed a gap in public sector marketing in city appearance branding in Depok City, which resulted in a decline in the city's image. However, there are findings of 2 (two) important things that affect the success of public sector marketing besides the 7Ps, namely participation and political will. Participation is in the form of community involvement in planning, implementing and monitoring policy products so that people feel ownership and pride, as well as political will related to leadership, authority and resource allocation. In this research, a  new concept is found, where when the concept of public sector marketing crosses the formal object of government science (authority, government relations, services), an adaptation of the concept into government marketing (Gov-Mark 9Ps) is born, which includes Product, Price, Place, Promotion, People, Physical Evidence, Process, Participation and Political Will in government relations. In conclusion, a more structured and adaptive government marketing model, especially in the city appearance branding policy, is needed to improve the city's positive image and public trust.gb777